Proposed Strategies For Expansion And Competitive Edge In Providing Professional Services - Leng, Leong Wai (2007)
This case study is divided into 2 sections: Case Writing and Case Analysis. Case Writing provides the background and information on the accounting profession in general and Accosec Corporate Services Sdn Bhd (ACSSB), its organizational structure, achievements, services and financial information in particular. The Case Analysis section highlights an environmental analysis, SWOT Analysis, financial analysis, customer analysis, competitive analysis and diagnosis of ACSSB. This section concludes with the formulation and execution of strategies, using the TOWS matrix analysis, for expansion and obtaining a competitive edge in providing professional services.